Analysis Of Tourism Development Strategy Of Long Beach In Bengkulu City - Nadya AL Nafturahma; Ida Angriani; Suswati Nasution (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
This study aims to find out the tourism development strategy for Panjang Beach in Bengkulu City using SWOT Analysis. The research method used in this research is descriptive qualitative, data collection techniques by distributing questionnaires to respondents and interviews with beach managers. The analysis method used is SWOT, namely identifying Strengths, Weaknesses, Opportunities and Threats. The research results show that the Pantai Panjang tourist attraction in Bengkulu City is in quadrant II. This means that the strategy used is a diversification strategy. The right combination of strategies to use is ST (Strength-Threats), namely by using all strengths to overcome all forms of threats, such as the following: the management can optimize the natural potential and uniqueness of the tourist attraction by sustaining and nurturing the tourist attraction on an ongoing basis and exercising firm control, maintaining all existing facilities at tourist locations, establishing cooperation between the private sector, government and the community in creating new innovations so that they are not inferior to other tourist attractions.